Underwater Light Characteristics of Turbid Coral Reefs of the Inner Central Great Barrier Reef - Jones, Ross; Pineda, Mari-Carmen; Luter, Heidi M.; Fisher, Rebecca; Francis, David; Klonowski, Wojciech; Slivkoff, Matthew (Frontiers in Marine Science, 2021)
Hyper-spectral and multi-spectral light sensors were used to examine the effects of elevated suspended sediment concentration (SSC) on the quantity and quality (spectral changes) of underwater downwelling irradiance in the turbid-zone coral reef communities of the inner, central Great Barrier Reef (GBR). Under elevated SSCs the shorter blue wavelengths were preferentially attenuated which together with attenuation of longer red wavelengths by pure water shifted the peak in the underwater irradiance spectrum 100 nm to the less photosynthetically useful green-yellow waveband (peaking at 575 nm). The spectral changes were attributed to mineral and detrital content of the terrestrially-derived coastal sediments as opposed to chromophoric (coloured) dissolved organic matter (CDOM). A simple blue to green (B/G, λ455:555 nm) ratio was shown to be useful in detecting sediment (turbidity) related decreases in underwater light as opposed to those associated with clouds which acted as neutral density filters. From a series of vertical profiles through turbid water, a simple, multiple component empirical optical model was developed that could accurately predict the light reduction and associated spectral changes as a function of SSC and water depth for a turbid-zone coral reef community of the inner GBR. The relationship was used to assess the response of a light sensitive coral, Pocillopora verrucosa in a 28-d exposure laboratory-based exposure study to a daily light integral of 1 or 6 mol quanta m2. PAR with either a broad spectrum or a green-yellow shifted spectrum. Light reduction resulted in a loss of the algal symbionts (zooxanthellae) of the corals (bleaching) and significant reduction in growth and lipid content. The 6 mol quanta m2 d−1 PAR treatment with a green-yellow spectrum also resulted in a reduction in the algal density, Chl a content per cm2, lipids and growth compared to the same PAR daily light integral under a broad spectrum. Turbid zone coral reef communities are naturally light limited and given the frequency of sediment resuspension events that occur, spectral shifts are a common and previously unrecognised circumstance. Dedicated underwater light monitoring programs and further assessment of the spectral shifts by suspended sediments are essential for contextualising and further understanding the risk of enhanced sediment run-off to the inshore turbid water communities.